2016
DOI: 10.1177/0959683616670470
|View full text |Cite
|
Sign up to set email alerts
|

Blame it on the goats? Desertification in the Near East during the Holocene

Abstract: The degree to which desertification during the Holocene resulted from climatic deterioration or alternatively from overgrazing has puzzled Quaternary scientists in many arid regions of the world. In the research reported upon here, a multi-disciplinary investigation of a 5-m deep, ~11,000-year-old sediment column excavated in a dry lake bed in southern Jordan revealed an early interval in which proxies of plant cover and sheep/goat stocking rates co-varied directly with climatic cycles. Beginning ~5.6 kcal BP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Higher stocking rates may have led to ecological degradation and desertification associated with overgrazing. Desertification as a result of overgrazing has been recorded in dryland environments across the world [ 77 and references therein], including in the modern Levant [ 78 ] and in Late Chalcolithic and Early Bronze Age Jordan, again linked to overstocking for commercialized textile production [ 79 ]. Within our study area, land use reconstructions based on archaeobotanical data have shown an increase in desert-steppe environments in the Jazira during the Middle Bronze Age (4,000–3,800 cal BP) when compared to the Early Bronze Age (5,000–4,000 cal BP), attributed to ecological degradation caused by both overgrazing and agricultural intensification [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher stocking rates may have led to ecological degradation and desertification associated with overgrazing. Desertification as a result of overgrazing has been recorded in dryland environments across the world [ 77 and references therein], including in the modern Levant [ 78 ] and in Late Chalcolithic and Early Bronze Age Jordan, again linked to overstocking for commercialized textile production [ 79 ]. Within our study area, land use reconstructions based on archaeobotanical data have shown an increase in desert-steppe environments in the Jazira during the Middle Bronze Age (4,000–3,800 cal BP) when compared to the Early Bronze Age (5,000–4,000 cal BP), attributed to ecological degradation caused by both overgrazing and agricultural intensification [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher stocking rates may have led to ecological degradation and desertification associated with overgrazing. Desertification as a result of overgrazing has been recorded in dryland environments across the world[77 and references therein], including in the modern Levant[78] and in Late Chalcolithic and Early Bronze Age Jordan, again linked to overstocking for commercialized textile production[79].…”
mentioning
confidence: 99%
“…Rapid anthropogenic deforestation and/or overgrazing of soils in the context of progressive reduction of water availability [94] may have enhanced the effect of surface processes leading to the dismantling and removal of the pristine Holocene soil cover. Elsewhere, prehistoric and historical records point to the coupled effect of climatic changes-triggered surface processes and human agency as a major cause of soil loss [14,15,29,[95][96][97][98][99][100].…”
Section: Evidence Of Climate Change At Tegole DI Bovinomentioning
confidence: 99%
“…The causes and extent of the drift sand landscape instability phases are currently not well understood for either European drift sand landscapes nor desertification (e.g. Fanta and Siepel, 2010;Henry et al, 2017). In part, this is because understanding causes and effects through time and space when there are multiple variables, each with their own leads and lags, is a not trivial exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Landscape instability of the drift sands as well as desertification processes have been variously attributed to climate, growing population pressure, agricultural overexploitation, increased mobility and usage of roads during the later Middle Ages (Castel, 1991;Cordova, 2007;Derese et al, 2010;Heidinga, 2010;Koster, 2010;Rosen, 2011;Fan et al, 2016;Henry et al, 2017;Pierik et al, 2018). For the European coversand belt it was originally thought that drift sand phases increased significantly after 1200 AD (Castel, 1991;Koster, 2010;Vera, 2011).…”
Section: Introductionmentioning
confidence: 99%